Backward Integration as a Business Strategy to Increase Company Profitability - Pratama Napitupulu, Binsar Energia (Riviera Publishing, 2022)
PT. Graha Alam Indo Sentosa is a developer operating in the real estate industry. Budiman Napitupulu and his son Binsar Napitupulu founded the company in 2017 in Semarang, Central Java. The organization prefers to construct housing zones for low- to middle-income people. The program is known as